In Vitro Fermentation of Rice Bran by Ruminococcus Sp. for Desirable Chemical Changes as Feed for Livestock (Global Journal of Medical Research, 2020)
Using rice bran in broiler diets has limitation due higher content of fiber and lower availability of few micronutrients including phosphorus. So, they were fermented anaerobically using 10% Ruminococcus albus isolated from rumen of cattle to get fermented value-added feed ingredient. It was fermented for 48 hours at 39 °C giving 60% moisture at different conditions like FRB (Rice Bran treated with Ruminococcus sp.), UFRB (Rice Bran treated with 2.0% urea using Ruminococcus sp.), MFRB (Rice Bran treated with 5.0% molasses using Ruminococcus sp.), UMFRB (Rice bran treated with 2% urea & 5% molasses using Ruminococcus sp.). The protein content was increased in UFRB (18.43%), UMFRB (17.19%) in comparison to RB group (14.42%) where UFRB showed highest crude protein (p
Keywords: in vitro; fermentation; ruminococcus spp rice bran; feed